2020
DOI: 10.1016/j.nbscr.2020.100058
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of the circadian and immune system: Desynchrony as a pathological outcome to traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a complex and costly worldwide phenomenon that can lead to many negative health outcomes including disrupted circadian function. There is a bidirectional relationship between the immune system and the circadian system, with mammalian coordination of physiological activities being controlled by the primary circadian pacemaker in the suprachiasmatic nucleus (SCN) of the hypothalamus. The SCN receives light information from the external environment and in turn synchronizes rhythms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 247 publications
0
6
0
Order By: Relevance
“…CR genes regulate pathogen recognition and cytokine secretion. [17,18] Guerro-Vargas et al demonstrated the involvement of the SCN in the regulation of inflammatory responses. Mice with an absent SCN exhibited an extreme and lethal proinflammatory response to stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…CR genes regulate pathogen recognition and cytokine secretion. [17,18] Guerro-Vargas et al demonstrated the involvement of the SCN in the regulation of inflammatory responses. Mice with an absent SCN exhibited an extreme and lethal proinflammatory response to stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…TBI-induced circadian disruption may be caused by many brain functions, e.g., circadian hormone regulation and neurotransmitter functions [ 46 ]. Neuroinflammation due to brain injury may also initiate a prolonged immune response that changes the expression of clock genes in the SCN and circadian function [ 47 , 48 ]. Clinical findings suggest two common types of post-TBI circadian rhythm disorders, including delayed sleep phase syndrome and irregular sleep-wake patterns [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TBI patients, those with cervical spinal cord injury commonly develop sleep disorders that are accompanied by circadian disruptions like dysregulated circadian rhythm and course of melatonin production [ 223 , 224 ], core body temperature [ 225 ], and aberrant expression patterns of clock genes in peripheral blood mononuclear cells [ 226 ]. Sleep abnormalities have been shown to negatively affect the outcome of TBI [ 227 ], and a recent study in mice shows involvement of circadian regulation in the neuroinflammation and blood–spinal cord barrier disruption following TSCI [ 228 ]; therefore, different kinds of chronotherapeutics have already been clinically tested. Blue-wavelength light therapy seemed to be helpful for patients with mild TBI or long-term fatigue following TBI [ 229 , 230 ].…”
Section: Interaction Of Tsci and Tbimentioning
confidence: 99%
“…Melatonin preconditioning of these cells could improve their regenerative potential [ 298 , 299 , 300 ]. As TSCI and TBI both negatively affect circadian rhythm as well as circadian-mediated inflammatory and healing cascades [ 227 , 233 , 301 , 302 ], chronotherapeutic aspects in MSC therapy for TSCI should be considered.…”
Section: Tbi Tsci and Mscsmentioning
confidence: 99%